Relación entre clima social familiar y las Manifestaciones sexuales observables en los Estudiantes de secundaria de la Institución Educativa Elsa Perea Flores- Tarapoto, Mayo – Agosto 2015 - Carrasco Pinedo, Karla Paquita (2015)
This study aimed to establish the relationship between family social climate And observable sexual demonstrations of high school students from the Educational Institution Perea Elsa Flores Tarapoto, May-August 2015 "; Quantitative explanatory, prospective, cross-sectional study, whose sample Was 107 students, the instrument gather data was the questionnaire Moos Test to measure the family social climate and questionnaire observable Sexual manifestations, validated by experts, the data was organized based Excel 2010 and SPSS software. V.22. The results were: Teens secondary education II.EE. Elsa pereflores a Tarapoto, May to August 2015, were characterized by being male with 52.3% (56); 61.7% (66) came from rural area; 43.9% (47) parents are Cohabiting marital status; 56.1% (60) belong to the nuclear family. Also Show a familiar social climate of medium or authoritarian with 69.2% (74) Related to the development dimension mainly with 75.7% (81). The most Common manifestation is observable sexual masturbation 65 (60.8%). In conclusion: Teens secondary education II.EE. Elsa Perea Flores - Tarapoto, May-August 2015, presented as family social climate of greater Association with the development dimension masturbation as sexual Observable manifestation, X2 = 3.981, p = 0.045 being <0.05.